Modeling of Soil Functions for Assessing Soil Quality: Soil Biodiversity and Habitat Provisioning - van Leeuwen, Jeroen P.; Creamer, Rachel E.; Cluzeau, Daniel; Debeljak, Marko; Gatti, Fabio; Henriksen, Christian B.; Kuzmanovski, Vladimir; Menta, Cristina; Pérès, Guénola; Picaud, Calypso; Saby, Nicolas P. A.; Trajanov, Aneta; et al. (Frontiers in Environmental Science, 2019)
Soil biodiversity and habitat provisioning is one of the soil functions that agricultural land provides to society. This paper describes assessment of the soil biodiversity function (SB function) as a proof of concept to be used in a decision support tool for agricultural land management. The SB function is defined as ‘the multitude of soil organisms and processes, interacting in an ecosystem, providing society with a rich biodiversity source and contributing to a habitat for aboveground organisms.’ So far, no single measure provides the full overview of the soil biodiversity and how a soil supports a habitat for a biodiverse ecosystem. We have assembled a set of attributes for a proxy-indicator system, based on four ‘integrated attributes’: 1) soil nutrient status, 2) soil biological status, 3) soil structure, and 4) soil hydrological status. These attributes provide information to be used in a model for assessing the capacity of a soil to supply the SB function. A multi-criteria decision model was developed which comprises of 34 attributes providing information to quantify the four integrated attributes and subsequently assess the SB function for grassland and for cropland separately. The model predictions (in terms of low – moderate – high soil biodiversity status) were compared with expert judgements for a collection of 137 grassland soils in the Netherlands and 52 French soils, 29 grasslands and 23 croplands. For both datasets, the results show that the proposed decision model predictions were statistically significantly correlated with the expert judgements. A sensitivity analysis indicated that the soil nutrient status, defined by attributes such as pH and organic carbon content, was the most important integrated attribute in the assessment of the SB function. Further progress in the assessment of the SB function is needed. This can be achieved by better information regarding land use and farm management. In this way we may make a valuable step in our attempts to optimize the multiple soil functions in agricultural landscapes, and hence the multifaceted role of soils to deliver a bundle of ecosystem services for farmers and citizens, and support land management and policy towards a more sustainable society.